Experiencia con la técnica Puzzle de Aronson para contenidos de cálculo diferencial - Vargas Cruz, Jorge Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The classroom experience exposed in this paper aims to use the Aronson method as facilitator of the collaborative learning process of contents of a course of differential calculus, in particular the limits of a continuous function of , form, with students of the third semester of Mathematics from Universidad Pedagógica y Tecnológica de Colombia, in order to see another possibility of teaching and learning in the classroom at undergraduate levels.